Environmental performance of window systems in patient rooms: a case study in the Belgian context. (August 2019) - Eisazadeh, N; De Troyer, F; Allacker, K
Abstract: Hospitals produce high amounts of emissions due to their continuous operation, high flow of people, and intensive HVAC requirements. In order to reduce the environmental footprint of hospitals, it is crucial to improve energy performance while still maintaining a comfortable indoor environment for the occupants. Also to avoid high environmental burdens, it is important to understand the impact of building material selection from the full life cycle perspective. Window systems influence the energy loads and comfort in buildings and provide access to daylight and views. Therefore, windows contribute significantly to the energy consumption and indoor environmental quality of buildings and impact the well-being of occupants. The aim of this study is to determine the influence of various window system design configurations on the environmental performance of patient rooms in Belgium through life cycle assessment (LCA). The method is innovative as it combines dynamic energy simulations and daylight analysis and integrates these in the LCA study of the window systems. The influence of several components is investigated, such as the choice of glazing and shading system. The results are analysed and compared in terms of energy cost for heating, cooling, and lighting, daylighting performance and life cycle environmental impacts. A typical patient room from a hospital design in Belgium is used as a case study. Based on comparative analysis, the paper discusses potential window system design configurations that allow for energy efficient, daylit and environmentally-friendly patient rooms.